Multilayer Immunohistochemical Analysis of Brain Tissue in Severe Traumatic Brain Injury - Chloe L. T. Kam; Cengiz Guner; Shumaila Hasan; Christopher E. G. Uff; Ping K. Yip (Proceedings)
Severe traumatic brain injury (TBI) is a complex disease, and understanding its injury-induced cellular pathobiology is vital to predicting outcomes and providing effective treatment and precision healthcare [...]